Comprehensive review of myalgic encephalomyelitis/chronic fatigue syndrome - Madhan Jeyaraman; Naveen Jeyaraman; Swaminathan Ramasubramanian; Luise Schäfer; Filippo Migliorini; Sangeetha Balaji (Journal of Translational Medicine, 2026)
Abstract Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a complex, debilitating disease that is unexplained and is characterised by persistent unexplained fatigue, Post Exertional Malaise (PEM), cognitive impairment, unrefreshing sleep and multisystem impairment. Despite the high burden of symptoms and the worldwide prevalence, ME/CFS has been poorly understood, underdiagnosed and underfunded. This large-scale review summarises the available evidence regarding the epidemiology, diagnostic progress, main clinical characteristics, pathophysiological theories and therapeutic approaches for ME/CFS. Despite problems with diagnostic consistency, the lack of validated biomarkers, and historical linkage to psychiatric illness, the recognition of this condition has been delayed and has led to patient marginalisation. The review highlights PEM as a cardinal symptom and reviews the weaknesses in earlier diagnostic criteria, as well as current changes in treatment guidelines, including the formal withdrawal of Graded Exercise Therapy, which has evidence of harm. New pathophysiological evidence suggests mitochondrial dysfunction, immune dysregulation, autonomic imbalance, neuroinflammation, and alterations in gut microbiome. New diagnostic and therapeutic strategies, such as metabolomic and electrophysiological assays, mTOR inhibitors, and decentralised clinical trial designs, are being studied. This intersection with Long COVID offers a chance to rapidly advance studies of post-infectious chronic diseases. The paper also argues for stringent subtyping, uniform data collection, and ongoing patient participation in research as strategies to surmount challenges of heterogeneity. Finally, it underscores the critical need for fair funding of research, so biomarker discovery and development of disease-modifying treatments can be achieved. The care of people with ME/CFS is not only a clinical obligation, but also a public health one.